Linking supportive leadership to satisfaction with care: proposing and testing a service-profit chain inspired model in the context of elderly care. Issue 4 (1st March 2021) - Kazemi, Ali; Elfstrand Corlin, Tinna
Abstract : Purpose: As marketization has gained ground in elderly care, satisfaction with care has come to play a crucial role in designing for high-quality care. Inspired by the service-profit chain (SPC) model, the authors aimed to gain a deeper understanding of the intricate interplay between supportive leadership practices, organizational climate, job satisfaction and service quality in predicting satisfaction with care. Design/methodology/approach: A Swedish sample of frontline elderly care staff ( n = 1, 342) participated in a cross-sectional questionnaire study. Mediation analyses were conducted to test the proposed model. Findings: As predicted, engaging in supportive leadership practices was directly and positively associated with satisfaction with care. In addition, as predicted, this relationship was partially mediated by organizational climate and job satisfaction. Moreover, job satisfaction predicted satisfaction with care with service quality explaining a statistically significant part of this relationship. Practical implications: Managers in elderly care services may improve satisfaction with care in multiple ways but primarily by showing that they care about the staff and ensuring that they are satisfied with their working conditions. Employee job satisfaction seems to be particularly crucial for satisfaction with care, beyond what can be accounted for by care service quality. Originality/value: The authors proposed a novel service-outcome model. Adding to the original SPC model, the model in this study suggested previously unexplored relationships including a direct path between leadership practices and satisfaction with service and a multiple-mediator model explaining this relationship. Also, new measures of organizational climate and supportive leadership were developed for which satisfactory reliability estimates were obtained.